Zirconia Inlay on Vital Teeth with Profunda Caries - Sandra Kartika Sari; Kun Ismiyatin; Bagus Aji Wibowo; Rara Amorita Miranda (Conservative Dentistry Journal, 2021)
Background: Dental caries has historically been considered the most critical component of the global burden of oral disease. Health facilities and dental health education counselling have been conducted, but public knowledge about dental caries is still low. The increasing number of dental caries is currently influenced by one of the factors of community behaviour. Most people do not realize the importance of taking care of oral and dental health. The ignorance of the community results in a decrease in productivity due to the influence of the perceived illness. Advances in dentistry since the last decade has allowed the use of conservative dental care. Modern restorative dentistry offers many methods for restoring teeth, both direct and indirect. The need for restoration of posterior teeth is related to aesthetic purposes and functional, biocompatibility and biomechanical aspects of the remaining tooth structure. Some materials that are widely used as tooth-coloured indirect restorations in posterior teeth are zirconia. Zirconia has its characteristics, especially in terms of functionality, such as mechanical strength, physical strength and aesthetics. Purpose: This study aims to determine the management of indirect restoration treatment using zirconia inlay on upper premolar. Case(s): A 46-yearold male patient complained that the filling of his upper left tooth was often loose and uncomfortable when used for eating because the food was stuck in it. The patient wants his teeth treated. The history of treatment on the tooth in question has been patched two times, but it often comes off partially. Case Management: From the examination that has been carried out, a clinical diagnosis of reversible pulpitis was established. The treatment plan that will be carried out is indirect pulpcapping using MTA and resin-modified glass ionomer cement as the base material. The planned restoration treatment is a fixed inlay restoration made of monolithic zirconia. Conclusion: Recently, zirconia has also been developed staining with improved translucency so that it becomes more aesthetic. Zirconia has a higher level of material resistance than otherrestorative materials such as composites. This is what makes zirconia the choice, especially for use as a framework for all-ceramic and partially-fixed crowns dental prosthesis.